PENINGKATAN KETERAMPILAN MENULIS KEMBALI ISI DONGENG DENGAN MEDIA AUDIOVISUAL BAGI SISWA KELAS III SDN 2 MRANTI KABUPATEN PURWOREJO SEMESTER GENAP TAHUN AJARAN 2015/2016 - Radityawati, Khoirum (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Improving Writing Skills of Folklore Using Audiovisual Media for the Third Grade Students of SD Negeri 2 Mranti at Purworejo Regency in the Academic Year of 2015/2016. The objective of this research is to improve writing skills of folklore using audiovisual media. This research is a collaborative Classroom Action Research (CAR) and each cycle consistsof planning, action, observation, and reflection. Subjects of the research were 36 students of third grader. Techniques of collecting data were observation, interview, and test. The results of this research showed that there is an increase of writing skills of folkloreusing audiovisual media.The conclusion of thisresearchistheuse of audiovisual media in Indonesian language learning can improve writing skills of folklorefor the third grade students of SD Negeri 2 Mranti. Keywords: Audiovisual media, writing skills, folkloreAbstrak: Peningkatan Keterampilan Menulis Kembali Isi Dongeng dengan Media Audiovisual bagi Siswa Kelas III SDN 2 Mranti Kabupaten Purworejo Semester Genap Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan keterampilan menulis kembali isi dongeng dengan media audiovisual. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif, tahapannya perencanaan, pelaksanaan, observasi, refleksi. Subjek penelitian siswa kelas III berjumlah 36 siswa. Hasil penelitian menunjukkan bahwa ada peningkatan keterampilan  menulis kembali isi dongeng menggunakan media audiovisual. Pengumpulan data dengan observasi, wawancara, dan tes. Kesimpulan penelitian yaitu penerapan media audiovisual dapat meningkatkan keterampilan menulis kembali isi dongeng pada siswa kelas III SD Negeri 2 Mranti. Kata Kunci: Media Audiovisual, Keterampilan menulis, Dongeng